دعوت و تبلیغ کی حکمت عملی،تعلیماتِ نبوی ﷺ کی روشنی میں - ڈاکٹر حافظ محمد سجاد (FIKR-O NAZAR فکر ونظر, 2010)
In view of Quranic verses and Ahadith of Prophet Muhammad (ﷺ) the meaning of Dawah wa Tabligh can be determined as to present the teachings of Islam to the people in such a well organised and dignified way, and with wisdom that the invitee or addressee may accept it easily realizing that it is an honour for him. Dawah with wisdom is one of the basic requirements for the preaching of Islam, without that, preaching or Dawah remains ineffective and useless. Wisdom of Dawah means to consider the psychological condition of the invitee or addressee. Psychological condition includes his mental level, capacity and personal circumstances. Thus, as much as the Da’ee or preacher be trained and expert of human psyche, the more result-oriented will be the Dawah. In Dawah methodology following aspects play very important role: Personal character and morals of the Da’ee or preacher, Restlessness in the Da’ee for reformation of the invitee or addressee, Gradual procedure of Dawah, Polite and lenient attitude for offering Dawah, Easy way for the presentation of Islamic teachings, Offering Dawah through motivation and inducement, Presentation of Dawah avoiding fully the attitude of compulsion or forcing. It is a fact that the principles and methodology of Dawah have been performed and guided so clearly through the revealed knowledge and its interpretation of Prophet Muhammad (ﷺ) that no other religion—revealed or unrevealed—can claim or present such a wonderful example of the principles and methodology of Dawah. It is only the pride and uniquness of Islamic Dawah performed by the Prophet Muhammad (S.A.W). It was the result of the methodology of Dawah adopted by the last messenger and the benefactor of the humanity for the character building of the society that many role models had prepared for the future of Muslim Society. They will remain the role models and minarates of the light forever for the future generations of the world till the end of this worldly life. This human psychological consideration of Dawah methodology and his (ﷺ ) personal practical model was brought about the great success of the Prophet Muhammad (ﷺ)’s teachings.